Answer:
The answer is 7(8 + 3)
Step-by-step explanation:
7 x 8 = 56
7 x 3 = 21
pls mark brainlyest:)
Answer:
Step-by-step explanation:
hey i got the answer straight from my teach but ony a and c if you have the answer to b let me know : ( A) To determine the mean absolute deviation, first calculate the mean. Find the sum of the values: 8 plus 6 plus 9 plus 6 plus 14 plus 9 plus 5 plus 7 equals 64. Then divide the sum by the number of values: 64 divided by 8 equals 8. The mean is 8.
Next, find the distance of each value from the mean :
|8-8|=0 |6-8|=2 |9-8|=1 |6-8|=2 |14-8|=6 |9-8|=1 |5-8|=3 |7-8|=1
0 plus 2 plus 1 plus 2 plus 6 plus 1 plus 3 plus 1 equals 16. Then divide the sum of absolute deviations by the number of data values: 16 divided by 8 equals 2. The MAD of the data is 2.
C. Since the MAD for the vegetable plant data is so much higher than the MAD for the flower data, this indicates that the heights of the vegetable plants vary more than the heights of the flowers ALSO do you go to k12
Answer:
Step-by-step explanation:
It seems this system of equations would be solved easier using the elimination method (the x and y values are lined up).
Multiply everything in the first equation by -2 (we want the 4x to be able to cancel out with a -4x).
Now line up the equations (they are already lined up - convenient) and add them from top to bottom.
The -4x and 4x are opposites, so they cancel out.
Adding 6y and 2y gives you 8y, and adding -12 and 4 gives you -8.
Divide both sides by 8.
Since you have the y-value you can substitute this in to the second (or first equation, it doesn't necessarily matter) equation.
Simplify.
Add 2 to both sides.
Divide both sides by 4.
The final answer is .
Answer:
a). x + y + 90° = 180°
b). x = 67°
y = 23°
Step-by-step explanation:
The sum of all angles in a triangle is 180°.
One of the angles in the figure is a right angle, or 90°. Therefore the sum of the three angles in the figure is:
x + y + 90 = 180
We are also told that x + 2 = 3y.
Rearranging that to isolate x gives us:
x = 3y - 2
Thake the first equation and substitute the above expression of in place of x:
x + y + 90° = 180°
(3y-2) + y + 90° = 180°
4y + 88° = 180°
4 y = 92°
y = 23°
To find angle x, use y = 23°
x = 3y - 2
x = 3*(23°) - 2
x = 67°
The sum 90° + 67° + 23° = 180°